Transmission line method for the simulation of Fiber Bragg Gratings - Stathopoulos, Nikolaos A.; Savaidis, S. P.; Simos, H.; Rigas, Evangelos; Correia, Ricardo N.; James, Stephen W.; Tatam, Ralph P. (Optical Society of America, 2019)
A new method for the analysis and design of fiber Bragg gratings (FBGs) based on the theory of transmission lines has been developed and verified both theoretically and experimentally. The method is an extension of the coupled-mode theory and utilizes the equivalent transmission lines in order to simulate any type of grating, with an easy and direct implementation. The method provides the ability to analyze the optical devices without using full wave approaches, while also facilitating the incorporation of core materials with a complex or non-linear refractive index, non-uniform distributions of the grating&\#x2019;s refractive index, and tilted and phase-shifted gratings. The approach also allows the design of the grating for a given reflection spectra. Numerical results of the method&\#x2019;s application on a randomly varied inscription of the refractive index of a FBG have also been simulated and discussed. Using this method, the characteristics of an erbium-doped (ED)-FBG have been simulated and the predictions verified experimentally.
Keywords: Dispersion compensation devices; Long period gratings; Reflection coefficient; Refractive index; Wavelength division multiplexing